Aging and Death in an Organism That Reproduces by Morphologically Symmetric Division - Stewart, Eric J; Madden, Richard; Paul, Gregory; Taddei, François (PLOS Biology, 2005)
Detailed time lapse photography reveals that organisms that divide symmetrically, such as the bacterium E. coli, can indeed age and consequently that no organism is immune to mortality.